Interprofessional Team Approach: Incorporating Oral Health to Improve Patient Outcomes for Older Adults - Ruth Goldblatt; David Henderson; Miranda Jennings (Association of American Medical Colleges, 2013)
Abstract This module will provide an understanding of the context in which a primary care provider will be requesting a dental consult in order to provide dental treatment to a patient. The student will learn when it is appropriate to make a dental referral and also how to complete a request for a consultation from a dentist. The student will also be able to incorporate examples of oral health promotion and prevention in medical practice. This document was developed to assist medical students in understanding the important role they have in recognition of oral health issues in their patients' lives, especially older adults. In working with interprofessional teams, it is apparent how even a small amount of oral health education and awareness can impact how medical students (pharmacy, nursing, and physician assistant students as well) engage in oral health efforts and make a difference in patients' lives. This module is an attempt to put a portion of that in writing to hopefully open the doors of communication between the dental and medical community by seeing the other side of the issue. This is meant to put a few tools in the toolbox that primary medical care providers need to help them provide and facilitate holistic care for their patients.